2020
DOI: 10.3389/fmicb.2020.00621
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Damages the Cell Surface of Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is currently regarded as one of the most important drug-resistant pathogens causing nosocomial and communityacquired infections. Although berberine (BER) has shown anti-MRSA activity, the underlying mechanism is still unclear. In this study, the damage caused by BER on the cell surface of MRSA was systematically investigated by performing BER susceptibility test, determining K + and alkaline phosphatase (ALP) release, detecting morphological alterations using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Zhang et al found that BER could damage the cell surface of MRSA. 43 Therefore, it is reasonable to speculate that the substances may include the contents of punched bacterial cells due to BER treatment. This observation is consistent with the above findings, illustrating that BER can destroy MRSA cell walls in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that BER could damage the cell surface of MRSA. 43 Therefore, it is reasonable to speculate that the substances may include the contents of punched bacterial cells due to BER treatment. This observation is consistent with the above findings, illustrating that BER can destroy MRSA cell walls in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Solasodine (3) and Tomatidine (4) are essential glycoalkaloid metabolites isolated from the Solanaceae genus [ 121 ]. These molecules are well-known for decades for their biological activity and as starting compounds for synthesizing steroid drugs [ 122 ]. According to a recent study, genomic analysis was performed to identify the cause of resistance in MRSA .…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…According to the existing research, the antibacterial effect of berberine can be generally summarized as “multi-effect” (Karaosmanoglu et al, 2014 ). Berberine can inhibit the formation of biofilm (Zhang et al, 2020 ; Bhatia et al, 2021 ; Xu et al, 2021 ), destroy the cell wall and cell membrane (Karaosmanoglu et al, 2014 ; Zhang et al, 2020 ; Xia et al, 2022 ), inhibit bacterial cell division (Domadia et al, 2008 ), inhibit nucleic acid and protein synthesis (Du et al, 2020 ), and inhibit bacterial adhesion (Kang et al, 2015 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental evidence shows that berberine alone or in combination with other agents showed obvious antimicrobial effects in vivo and in vitro (Aksoy et al, 2020 ; Huang et al, 2020 ; Xie et al, 2020 ; Bhatia et al, 2021 ). Berberine even has the potential to inhibit antibiotic-resistant bacteria (Morita et al, 2016 ; Zhang et al, 2020 ; Li et al, 2021 ), which gives it great potential in the development of new antibiotics. There are many studies on the antimicrobial activity of berberine, and it is found that berberine has a variety of antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%